Evaluasi Usability terhadap Sistem Informasi Antrian Rumah Sakit Krakatau Hospital System dengan Metode Pattern Based Usability Testing - Rahadyan Nandiwardhana; Widhy Hayuhardhika Nugraha Putra; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
This study aims to evaluate the quality level of usability based on the stakeholders demands of the company's by considering the usability criteria in the aspects of effectiveness, efficiency, and satisfaction. The object of this research is the information system of the krakatau hospital system owned by PT Krakatau Information Technology which is carried out on 2 different types of platforms, website platform and android platform. The evaluation method use pattern based usability testing which in the process contains the formation of usability patterns and testing scenarios, then use the usability criteria question of satisfaction aspects of the USE questionnaire. Data collection is done by the testing using work assignments to test respondents. The sample of this study was 10 test respondents with 2 different classifications, test respondents who had never used a similar system (respondent classification 0) and test respondents who had used a similar system (respondent classification 1), which were selected using the purposive sampling method. The results of this study get the formation of 4 work tasks on each platform based on the process of forming usability patterns and testing scenarios. The test results get measurements of the level of usability quality on 3 aspects of usability, finding 12 problems on the website platform, and 17 problems on the android platform. Formed 10 recommendations for improving the website platform problems and 10 recommendations for improving the android platform problems.